Leveraging local advantages abroad in volatile markets: Enka Engineering and Construction - Golgeci, Ismail (Henry Stewart Talks, 2021)
Surviving and thriving in volatile markets, Enka Engineering, Enka’s operations abroad, Enka: Navigating turbulent waters, Enka’s outcomes